Abundance profiles of Calanidae in the northern and southern Benguela Current upwelling system - Maya Bode-Dalby; Hanna Rittinghaus; Annabel Mathiske; Holger Auel; Hans M Verheye; Sabrina Dorschner; Wilhelm Hagen (PANGAEA, 2025)
This dataset includes abundances of Calanidae copepods, i.e. different developmental stages of Calanoides natalis, Calanus agulhensis, Nannocalanus minor, Mesocalanus tenuicornis, Neocalanus gracilis and Neocalanus tonsus, during the research cruise M153 with RV Meteor in the northern (nBUS) and southern (sBUS) Benguela Upwelling System between February 15 and March 28, 2019. The cruise was part of the TRAFFIC (Trophic tRAnsfer eFFICiency in the Benguela Current) project. Samples were retrieved from vertical multinet Midi hauls (200 μm mesh size). The aim was to identify distribution patterns in relation to environmental conditions and the comparison of horizontal, vertical and trophic niches of close-related, similar-sized key copepod species in the BUS.